Navigating Environmental Policy in North Bandung Area: Overcoming Implementation Barriers for Sustainable Governance - Abdullah, Muhammad Solihin; Rusli, Budiman; Darto, Darto (Journal Public Policy, 2025)
This study aims to answer the question: "What are the obstacles and challenges in implementing environmental policies in the North Bandung Area?" Using a qualitative case study approach, data were collected from key government policymakers, local communities, and environmental activists. Participants were selected through purposive and snowball sampling to capture diverse perspectives. Findings indicate that limited government support, inconsistent policy enforcement, and inadequate community engagement hinder effective policy implementation. Political pressure, weak inter-agency coordination, and insufficient funding further exacerbate these implementation gaps. To address these challenges, participatory and collaborative strategies utilizing systems thinking are essential to identify leverage points for sustainability. In conclusion, environmental policies in North Bandung face political, financial, and coordination constraints. Effective conservation requires strong political commitment, innovative financing, community involvement, digital monitoring tools, and lessons drawn from practices in Bali and Bogor. This study is limited by its focus on a single region within the KBU, so findings may not be generalizable to other conservation areas. Future research using mixed methods or comparative approaches is recommended to validate and expand upon these findings. Practically, the study offers actionable recommendations for policymakers, including adopting digital monitoring technologies, developing alternative financing strategies, and institutionalizing community participation in environmental governance